Opposite relationship between circulating soluble CD14 concentration and endothelial function in diabetic and nondiabetic subjects - Fernández-Real, José-Manuel; López-Bermejo, Abel; Castro, Antoni; Broch, Montserrat; Peñarroja, Georgina; Vendrell, Joan; Vázquez, Gabriel; Ricart, Wifredo (Thrombosis and Haemostasis, 2005)
Recent prospective studies indicate endothelial dysfunction and increased risk for cardiovascular events in patients with serological evidence of multiple infections. Soluble CD14 (sCD14) plays a key role in the neutralization of lipopolysaccharide (LPS), a well-established bacterial product inducing endothelial dysfunction. Insulin resistance was recently identified as a significant factor influencing circulating sCD14 concentration. Thus, we investigated the association of circulating sCD14 and endothelial dysfunction in subjects with well-established insulin resistance (patients with type 2 diabetes, n=40) compared to control nondiabetic subjects (n=100). To further explore the underlying mechanisms, we also analysed C-reactive protein and circulating NO2-/NO3- and cyclic GMP in the diabetic group. Serum sCD14 concentration (ELISA) was found to be differently associated with endothelium-dependent vasodilatation (EDVD, high-resolution ultrasound) in diabetic and non-diabetic subjects. In nondiabetic subjects, serum sCD14 and C-reactive protein correlated negatively with EDVD (r= −0.21, p=0.03, and r=−0.21, p=0.03, respectively). In a partial correlation analysis, these associations remained significant after controlling for age and weight (sCD14 and EDVD, r=−0.23, p=0.023; C-reactive protein and EDVD, r=−0.21, p=0.03; sCD14 and C-reactive protein, r=0.30, p=0.002). In contrast, sCD14 was positively associated with EDVD in type 2 diabetic patients (r= 0.37, p=0.019,). Interestingly, sCD14 was also associated with NO2-/NO3- in this group (r=0.62, p=0.001, n=22). EDVD also correlated with cyclic GMP (r=0.47, p=0.03, n=22). In summary, circulating sCD14 is associated with endothelial function. While in non-diabetic subjects sCD14 behaves as an acute phase reactant, its role in type 2 diabetic patients should be further clarified. These findings need to be confirmed in further studies with larger number of patients.
Keywords: Cytokines; atherosclerosis; diabetes / metabolic disorders; inflammatory mediators; ultrasound / diagnosis